2017
DOI: 10.1038/srep41388
|View full text |Cite
|
Sign up to set email alerts
|

Long-term and realistic global change manipulations had low impact on diversity of soil biota in temperate heathland

Abstract: In a dry heathland ecosystem we manipulated temperature (warming), precipitation (drought) and atmospheric concentration of CO2 in a full-factorial experiment in order to investigate changes in below-ground biodiversity as a result of future climate change. We investigated the responses in community diversity of nematodes, enchytraeids, collembolans and oribatid mites at two and eight years of manipulations. We used a structural equation modelling (SEM) approach analyzing the three manipulations, soil moisture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 71 publications
(88 reference statements)
2
17
0
1
Order By: Relevance
“…Although the reduction of soil moisture in warmed plots was small, it was consistent and statistically significant (Holmstrup et al. ). For some biological responses, even such minor changes in soil moisture may be important and therefore must be accounted for when trying to unravel the mechanistic interactions between organisms and the environment.…”
Section: Resultsmentioning
confidence: 65%
See 3 more Smart Citations
“…Although the reduction of soil moisture in warmed plots was small, it was consistent and statistically significant (Holmstrup et al. ). For some biological responses, even such minor changes in soil moisture may be important and therefore must be accounted for when trying to unravel the mechanistic interactions between organisms and the environment.…”
Section: Resultsmentioning
confidence: 65%
“…However, a number of interactions are inherent, such as the passive nighttime warming technique causing simultaneous reduction in soil moisture due to increased evaporation related to increased temperature, but likely also related to reduced dew formation during nighttime due to the coverage by the reflective curtains used for nighttime passive warming. Although the reduction of soil moisture in warmed plots was small, it was consistent and statistically significant (Holmstrup et al 2017). For some biological responses, even such minor changes in soil moisture may be important and therefore must be accounted for when trying to unravel the mechanistic interactions between organisms and the environment.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…Likely, the intensity of the warming applied was moderate not only for collembolans (although see Petersen, 2011, for a further discussion on the modest warming effects found in some of the sites) but also for plant communities and ecosystem functions like net primary productivity and respiration, which were also rather insensitive to the warming treatment (Kröel-Dulay et al, 2015;Reinsch et al, 2017). Recent findings have nonetheless revealed that springtails, and in general soil fauna, may be quite resistant to increases in temperature (Alatalo et al, 2015;Holmstrup et al, 2017Holmstrup et al, , 2018. Recent findings have nonetheless revealed that springtails, and in general soil fauna, may be quite resistant to increases in temperature (Alatalo et al, 2015;Holmstrup et al, 2017Holmstrup et al, , 2018.…”
Section: Discussionmentioning
confidence: 98%